Pengaruh Persepsi Harga dan Kualitas Produk Terhadap Kepuasan Pelanggan Produk Skincare Skintific - Bagus Setiawan; Eka Dyah Setyaningsih; Vina Islamy (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to analyze the effect of price perception and product quality on customer satisfaction of Skintific skincare products. Price perception refers to the amount of money exchanged for a product or service, while product quality consists of various attributes that influence how well a product meets customer expectations. A higher product quality increases a company's chance of attracting customers. This research employed a quantitative method with a sample of 100 Skintific consumers. Data were collected through observation and questionnaires. The results showed that price perception has a positive and significant effect on customer satisfaction, with a t-value of 11.889 (t count > t table: 11.889 > 1.988). Likewise, product quality also has a significant effect on customer satisfaction, with a t-value of 17.025 (t count > t table: 17.025 > 1.988). Furthermore, the F-test result showed that the calculated F (220.109) is greater than the F-table value (3.09), indicating that price perception and product quality simultaneously have a significant influence on customer satisfaction. These findings highlight the importance for companies to pay attention to both price perception and product quality to increase consumer satisfaction with skincare products.